The Dutch Strategic and Operational Approach in the Indonesian War of Independence, 1945-1949 - Scholtz, Leopold (Scientia Militaria, 2019)
The Indonesian War of Independence (1945–1949) and the Dutch attempt to combat the insurgency campaign by the Indonesian nationalists provides an excellent case study of how not to conduct a counter-insurgency war. In this article, it is reasoned that the Dutch security strategic objective – a smokescreen of autonomy while keeping hold of political power – was unrealistic. Their military strategic approach was very deficient. They approached the war with a conventional war mind-set, thinking that if they could merely reoccupy the whole archipelago and take the nationalist leaders prisoner, that it would guarantee victory. They also mistreated the indigenous population badly, including several mass murders and other war crimes, and ensured that the population turned against them. There was little coordination between the civilian and military authorities. Two conventional mobile operations, while conducted professionally, actually enlarged the territory to be pacified and weakened the Dutch hold on the country. By early 1949, it was clear that the Dutch had lost the war, mainly because the Dutch made a series of crucial mistakes, such as not attempting to win the hearts and minds of the local population. In addition, the implacable opposition by the United States made their war effort futile.